Implementasi Kepemimpinan Demokratis dalam Peningkatan Prestasi Olahraga Peserta Didik di SDN Pasirjambu - Suprianto, Hennry; Sumarno, Dedi; Yunara, Yunara; Muchtar, Hendi S; Handayani, Sri (Universitas Pendidikan Mandalika, 2024)
Abstract : This study explores the implementation of democratic leadership in improving student sports achievements at SDN Pasirjambu, focusing on how this leadership approach affects the development of sports programs and student engagement. The research questions are: first, how does the school principal's democratic leadership improve student sports achievements at SDN Pasirjambu? Second, how is democratic leadership implemented in improving student sports achievements at SDN Pasirjambu? Third, what are the barriers and challenges to democratic leadership in improving student sports achievements at SDN Pasirjambu? A qualitative method was used. Data were obtained in the field through in-depth, structured interviews, and from literary sources. Data from literature studies and field studies are presented as research findings. The displayed data are then abstracted to reveal facts. The next stage involves interpreting these data to produce information or knowledge. The conclusion of this research is that democratic leadership at SDN Pasirjambu, initiated by the school principal, plays a crucial role in enhancing student sports achievements. This approach recognizes and involves every teacher and student in sports-related decision-making, encouraging their active participation and contribution, and facilitating the development of innovative training methods and teacher professionalism. However, the implementation of democratic leadership faces obstacles, including limitations in resources and sports facilities, resistance to change from some teachers, and challenges in balancing the needs and desires of various students.Key Words: Leadership Implementation, Democratic Leadership, Sports AchievementAbstrak : Studi ini mengeksplorasi implementasi kepemimpinan demokratis dalam peningkatan prestasi olahraga peserta didik di SDN Pasirjambu, dengan fokus pada bagaimana pendekatan kepemimpinan ini mempengaruhi pengembangan program olahraga dan keterlibatan siswa. Pertanyaan dalam penelitian, pertama, bagaimana Kepemimpinan demokratis kepala sekolah dalam peningkatan prestasi olahraga peserta didik di SDN Pasirjambu. Kedua, bagaimana implementasi kepemimpinan demokratis dalam peningkatan prestasi olahraga peserta didik di SDN Pasirjambu. Ketiga, apa saja hambatan dan kendala kepemimpinan demokratis dalam peningkatan prestasi olahraga peserta didik di SDN Pasirjambu. Metode yang digunakan adalah kualitatif. Data diperoleh di lapangan melalui wawancara, mendalam, terstruktur dan dari sumber-sumber kepustakaan. Data hasil studi pustaka dan studi lapangan ditampilkan sebagai temuan penelitian. Data yang telah ditampilkan kemudian di abstraksikan yang bertujuan untuk menampilkan fakta. Tahap selanjutnya, data tersebut diinterpretasi untuk menghasilkan informasi atau pengetahuan. Kesimpulan dari penelitian ini yaitu; kepemimpinan demokratis di SDN Pasirjambu, yang diprakarsai oleh kepala sekolah, memegang peranan krusial dalam meningkatkan prestasi olahraga peserta didik. Pendekatan ini mengakui dan melibatkan setiap guru dan peserta didik dalam pengambilan keputusan olahraga, mendorong keterlibatan aktif dan kontribusi mereka, serta memfasilitasi pengembangan metode pelatihan inovatif dan profesionalisme guru. Namun, implementasi kepemimpinan demokratis ini menghadapi hambatan, termasuk keterbatasan sumber daya dan fasilitas olahraga, resistensi terhadap perubahan dari beberapa guru, serta tantangan dalam menyeimbangkan kebutuhan dan keinginan berbagai peserta didik.Kata Kunci: Implementasi Kepemimpinan, Kepemimpinan Demokratis, Prestasi Olahraga